Perbandingan Hukum Perzinahan dalam UU No. 1 Tahun 2023 tentang Kitab Undang-Undang Hukum Pidana (KUHP) dengan Hukum Islam - Wahyuningsih, Nunung Dian (Journal of Law, Society, and Islamic Civilization, 2023)
This study aims to find out how the adultery Article is regulated in the new Criminal Code from the Islamic law perspective. The method used in this study is normative legal research. Even though  there has been an update to the adultery provisions in the new Criminal Code, there are still pros and cons. Some people think that Article 411 in the Criminal Code is considered over-criminalized and the state is over-interfere in individual privacy. As an absolute complaint offense, this provision is considered have a loopholes for committing adultery and the light punishment does not deter the offender. Meanwhile, Islamic law explicitly emphasizes that adultery is a disgraceful act that destructive and can be subject to hudud sanctions which aimed to maintain the society. In addition, the punishment for adultery, which is considered cruel and have an embarrassing and deterrent effect on both the perpetrator and other people.